(untitled) (INNOVATIVE ECONOMY, 2026)
Savonik T.P. BANK LENDING AS A FACTOR IN UKRAINE’S ECONOMIC STABILITY UNDER MARTIAL LAW Purpose. The aim of the article is to assess the role of lending activities in ensuring the financial stability of the banking sector and national economic security, as well as substantiation of the key trends and strategic directions for improving bank lending in the current economic realities. Methodology of research. The methodological framework of the study is based on a set of methods: induction and deduction, used to identify current trends and patterns in the development of bank lending under martial law conditions; analysis and synthesis, applied to compare traditional and innovative approaches to credit operations management; the computational and constructive approach, employed to substantiate the potential of lending in maintaining financial stability and stimulating economic activity. Findings. The essence of lending activity as a key factor in the functioning of financial and credit institutions is examined. The fundamental role of bank lending and its crucial importance in stimulating entrepreneurial activity, maintaining the stability of the monetary and credit sphere, and promoting investment flows are substantiated. The necessity of optimizing credit policy in order to minimize the risks associated with the formation of non-performing assets and to provide targeted support for priority sectors of the national economy is identified. Particular attention is paid to the modernization of borrower creditworthiness assessment methodologies as an essential prerequisite for strengthening the stability of the banking sector and ensuring the economic security of the state. The transformational processes occurring in Ukraine’s credit market, driven by both wartime challenges and macroeconomic conditions, are investigated. A set of regulatory easing measures introduced by the National Bank of Ukraine within its regulatory framework governing credit risk assessment methodology is considered. Attention is focused on the clear trend toward reducing the share of foreign currency lending. This strategy contributes to mitigating currency risks and stabilizing macroeconomic processes. A distinction is made between gross and net credit obligations. A sectoral analysis is conducted, demonstrating the priority orientation of credit policy toward state-owned corporations. The distribution of loans by maturity is also analysed. It is proven that bank lending is a key factor in ensuring the financial stability and economic sovereignty of the state, and that its progressive development requires the formation of a proactive strategy focused on stimulating the real sector of the economy. Particular emphasis is placed on the role of state financial institutions within the stabilization mechanism, as they serve as primary institutions in maintaining financial stability and ensuring access to borrowed funds during periods of economic turbulence. The strategic importance of lending activity for achieving macroeconomic stability is substantiated, since lending operations ensure the continuity of cash flows and form the foundation of the national economy’s economic security. Based on the obtained findings, practical recommendations have been developed for both banking institutions and the state. These recommendations involve the creation of integrated financial ecosystems with adaptive instruments to support entrepreneurial activity. The key trends in the evolution of the loan capital market in the post-war period have been identified, particularly the strengthening of its adaptive capacity and its integration into the global financial architecture. Originality. The theoretical foundations of bank lending as a key mechanism for ensuring the financial stability of the domestic banking system under martial law have been further developed. Particular attention is focused on the fundamental role of state-owned banks. Their capacity, owing to their substantial scale and government support, to assume long-term risks and thereby ensure the stability of the financial system is substantiated. Strategic measures for commercial banks and the state have been developed with the aim of ensuring the effective functioning of the lending sector while simultaneously strengthening macroeconomic stability. Promising directions for the development of Ukraine’s credit market following the termination of martial law have also been proposed. Practical value. The obtained results can be used by public authorities and bank management as strategic guidelines for shaping lending policies under martial law conditions. The proposed innovative approaches to credit operations management contribute to enhancing the financial resilience of the banking system, ensuring macroeconomic equilibrium, and strengthening the economic security of the state. Key words: lending activity, bank lending, loan portfolio, financial stability, sustainable economic development, post-war recovery.